Coke tolerance of Ni/Al2O3 nanosheet catalyst for dry reforming of methane. Issue 7 (9th March 2016) - Kim, Won Yong; Lee, Young Hye; Park, Hunmin; Choi, Yo Han; Lee, Min Hee; Lee, Jae Sung
Abstract : In the dry reforming of methane with CO2, Ni/Al2 O3 nanosheet catalysts exhibited excellent coke tolerance, showing stability even in the presence of a large amount of coke because of the large intersheet pores. Abstract : In the dry reforming of methane with CO2, coke formation in the catalyst during the reaction is the most serious problem. As a coke resistant reforming catalyst, Ni/Al2 O3 nanosheets were synthesized by a solvothermal method. The synthesized nanosheet catalysts demonstrated highly stable methane conversion, although the amount of deposited carbon was similar to that in Ni/Al2 O3 with a random morphology that deactivated rapidly. The critical effect of nanosheet morphology has been demonstrated on the coke tolerance of the nickel-based dry reforming catalyst.